The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0100-67622013000400009
|View full text |Cite
|
Sign up to set email alerts
|

Fenologia de Dalbergia cearensis Ducke (Fabaceae) em um fragmento de floresta estacional, no semiárido do Nordeste, Brasil

Abstract: RESUMO -Em geral, espécies arbóreas que ocorrem na vegetação de Caatinga, no semiárido do Nordeste brasileiro, têm suas fenofases (floração, frutificação e mudança foliar) condicionadas pela duração e intensidade da seca sazonal. Este estudo registrou a fenologia da queda foliar, incisão, floração e frutificação em 32 indivíduos de Dalbergia cearensis. Os indivíduos foram amostrados a cada 15 dias em 2009-10 e 2010-11, na Unidade de Conservação de Uso Sustentável "Fazenda Não me Deixes", situada em Quixadá, Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…In short, in any exploitation system in the Caatinga, it is important to understand that the regulators of the vegetation dynamics are the water reserves of the soil, which are simultaneously associated with the rain pulses and inter-pulses. Investigating the phenology of Dalbergia cearensis Ducke (Fabaceae: Faboideae), an endemic deciduous species of the thorny xerophytic forest of northeastern Brazil, Nogueira et al (2013) also found that leaf sprouting was positively correlated with the average monthly precipitation and with the water availability in the soil and negatively correlated with the average monthly temperature and average insolation.…”
Section: Activity Index (Percentage Of Individuals)mentioning
confidence: 99%
“…In short, in any exploitation system in the Caatinga, it is important to understand that the regulators of the vegetation dynamics are the water reserves of the soil, which are simultaneously associated with the rain pulses and inter-pulses. Investigating the phenology of Dalbergia cearensis Ducke (Fabaceae: Faboideae), an endemic deciduous species of the thorny xerophytic forest of northeastern Brazil, Nogueira et al (2013) also found that leaf sprouting was positively correlated with the average monthly precipitation and with the water availability in the soil and negatively correlated with the average monthly temperature and average insolation.…”
Section: Activity Index (Percentage Of Individuals)mentioning
confidence: 99%
“…So, that the possibilities of water reserves become limited, resulting in greater sensitivity to soil water changes and to the water deficit, as measured by interpulse predominates over the precipitation pulses. According to Nogueira et al (2013) and Santos et al (2013), dense wood species are sensitive to water stress. They rapidly lose leaves as a way to reduce moisture loss.…”
Section: Leaf Senescencementioning
confidence: 99%
“…O acompanhamento fenológico foi realizado em 15 indivíduos de Q. multiflora. Os critérios para a escolha de árvores foram a aparente ausência de doenças e infestações por parasitas, diâmetro na altura do peito acima de 10 cm e copa totalmente visível (Nogueira et al 2013). Tais observações ocorreram mensalmente durante dois anos, tendo início em julho de 2016 e término em junho de 2018.…”
Section: Acompanhamento Fenológicounclassified